Novel urokinase-plasminogen activator inhibitor SPINK13 inhibits growth and metastasis of hepatocellular carcinoma in vivo. (May 2019) - Wei, Ling; Lun, Yongzhi; Zhou, Xiaoping; He, Shang; Gao, Lijuan; Liu, Yan; He, Zheng; Li, Baoming; Wang, Chengbin
Graphical abstract: Abstract: Advanced hepatocellular carcinoma (HCC) is a highly aggressive malignancy that is a serious threat to the public health system of China. Urokinase-plasminogen activator (uPA) can promote the invasive growth and metastasis of HCC cells by activating matrix metalloproteinases (MMPs), leading to the breakage of the extra-cellular matrix. uPA is a promising target for advanced HCC treatment. In this stuy the expression of uPA was examined by quantitative polymerase chain reaction in hepatic cell lines. Protein interaction between uPA and SPINK13 was identified by immunoprecipitation. In vitro biochemical assay was used to examine the inhibitory effect of the SPINK13 on the direct cleaving of the recombinant pro-MMP9 by uPA. The antitumor effect of SPINK13 was examined by transwell assay or the nude mice tumor model.The expression of uPA was much higher in highly aggressive HCC cell lines than in lowly aggressive HCC cell lines or non-tumor hepatic cell lines. SPINK13 interacted with uPA in HCC cells and directly inhibited the cleaving of MMP9 by uPA. Treatment of the recombinant SPINK13 protein inhibited the invasion of HCC cells in several experiments, such as transwell experiments or the intrahepatic growth model. The results of the study indicated that SPINK13 could function as a promising therapeutic approach for patients with advanced HCC.